Seeing Things: A Community Science Investigation into Motion Illusion Susceptibility in Domestic Cats (Felis silvestris catus) and Dogs (Canis lupus familiaris) - Smith G. E.; Chouinard P. A.; Lin I.; Tsoi K. T.; Agrillo C.; Byosiere S. -E. (Animals, 2022)
Simple Summary The study of visual illusion susceptibility offers a fascinating lens into the evolution of perception. Utilizing a community science paradigm, this study investigated pet dogs' and cats' susceptibility to the Rotating Snakes motion illusion. The results reveal that both species did not spend significantly more time at the illusion than at either of the controls, failing to indicate susceptibility to the illusion. These findings offer valuable information for the field of non-human animal geometric illusion research, both in terms of comparative perception and methodological practices. Illusions-visual fields that distort perception-can inform the understanding of visual perception and its evolution. An example of one such illusion, the Rotating Snakes illusion, causes the perception of motion in a series of static concentric circles. The current study investigated pet dogs' and cats' perception of the Rotating Snakes illusion in a community science paradigm. The results reveal that neither species spent significantly more time at the illusion than at either of the controls, failing to indicate susceptibility to the illusion. Specific behavioral data at each stimulus reveal that the most common behaviors of both species were Inactive and Stationary, while Locomotion and Pawing were the least common, supporting the finding that susceptibility may not be present. This study is the first to examine susceptibility to the Rotating Snakes illusion in dogs, as well as to directly compare the phenomenon between dogs and cats. We suggest future studies might consider exploring alternative methods in testing susceptibility to motion illusions in non-human animals.